Automatic Web Publishing - Sanchez-Vilar, Oscar (Trinity College Dublin. Department of Computer Science, 2000)
Research and Development departments of most important companies are currently producing technical documents and papers as a result of their own investigation projects. This type of documents normally develop concepts and ideas that often lead to a contribution to knowledge (or possibly to simple information) that may be interesting for other research projects in the department or for further investigation. In that kind of environments, a system for publishing and sharing information become a requirement for the success of the department. Although many approaches to solve this problem have already been considered, such as shared system files and mailing lists, all of them offer to the user limited services and require extra input information to know which documents are of interest to each user. Besides, the growing demand for web based interactive solutions and for personalization has made them become obsolete. This project will investigate the design of an automated system for the publication of technical documents on the World Wide Web. Using a simple interface, its distributed users will be able to publish the results of their research, and, automatically, the system will make the new document available for the rest of the users (once reviewed if necessary) by linking it from appropriate document collections, by building searching indices to allow to look for the document using keywords. The publication of a new document will be announced to potentially interested readers by emailing a notification to them; to decide who might be interested in a new document, the system will keep information about interests and past interactions with the system for each authorized user. Other features that the system will provide (if necessary) are the possibility of feedbacking information to report authors and publishing the same document in different formats.
Keywords: Computer Science